Systematic Review Relationship Between Cesarean Section Delivery And Asphycia Incidence - Simamora, Debora Lestari; Sinaga, Elvalini Warnelis (SEAN Institute, 2023)
We reviewed the outcome for 211 women undergoing a planned en caul (within intact membranes) cesarean section and for 836 control women with conventional lower segment section, in the period 2001–2010 at a university-affiliated hospital in China, where the former technique has been practiced. Of the intended en caul sections there were 141 successful deliveries (66.8%), and 70 that failed and were converted to conventional lower segment cesarean section. Maternal blood loss was similar for both operation types, but the rate of asphyxia was significantly lower among preterm infants delivered by the en caul method than in the control cases. Multivariate logistic regression revealed that the volume of amniotic fluid, a low Bishop score and high birthweight were associated with failed en caul deliveries. Cesarean section en caul can be a safer option than lower segment section when preterm delivery is required. Aretrospective cohort study was conducted inasingle tertiary center, between January 1st, 2007, and December 31st, 2017. The study included 62330 singleton pregnancies delivered after 24 0/7 weeks gestation. Multivariable analyses compared trauma atbirth cesarean sectin, birth hypoxia and birth asphyxia interm and preterm deliveries, stratified by mode ofbirth, VD versus CS. Main outcome measure was trauma atbirth including intracranial laceration and haemorrhage, injuries toscalp, injuries tocentral and peripheral nervous system, fractures toskeleton, facial and eye injury.